The system (picture found in attachment) is in static equilibrium, and the string in the middle is exactly horizontal.
a. Tension T1
b. Tension T2
c. Tension T3
d. angle (theta)
The Attempt at a Solution
a. Using Ty = T1sin60 - mg = 0, T1=34 N.
b. Using Tx = T2 - T1cos60 = 0, T2 = 17 N
c. Eq'n 1: Tx = T3sin(theta) - mg = 0
Re-arranged to: theta = cos-1 T2/T3
Eq'n 2: Ty = T3sin(theta) - mg = 0
Then I substituted the re-arranged eq'n (1) into eq'n (2), and I got this:
0 = T3sin(cos-1 T2/T3) - mg
However, I don't know how to solve this ... so I think I may be doing something wrong.
Thank you in advance for any assistance!